1977
DOI: 10.1029/ja082i016p02227
|View full text |Cite
|
Sign up to set email alerts
|

Auroral vector electric field and particle comparisons, 1, Premidnight convection topology

Abstract: The inverted V natuxe of the electron precipitations at the convection boundary, compared with the lack of such structure over the arc which was within the positive bay region, leads to the conclusion that auroral arcs are likely to be associated with inverted V type precipitation only at or poleward of convection boundaries and their eddy structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…The electric field was inferred from ion flow data and measured using double-probe techniques. In agreement with the results of MAYNARD et al (1977), they found noteworthy perturbations of the electric field direction at the borders of the arc, suggesting strong shear flow at the arc boundaries . Their results are not in accord with those of Maynard et al, in that within the visable arc the electric field was correlated with energetic electron flux rather than being anticorrelated.…”
Section: High Latitude Electric Fieldssupporting
confidence: 88%
See 2 more Smart Citations
“…The electric field was inferred from ion flow data and measured using double-probe techniques. In agreement with the results of MAYNARD et al (1977), they found noteworthy perturbations of the electric field direction at the borders of the arc, suggesting strong shear flow at the arc boundaries . Their results are not in accord with those of Maynard et al, in that within the visable arc the electric field was correlated with energetic electron flux rather than being anticorrelated.…”
Section: High Latitude Electric Fieldssupporting
confidence: 88%
“…Within the eastward electrojet the polarization electric field opposes the ambient electric field, and one would then expect an anticorrelation of electric field and precipitating electron flux. Thus, the fact that the results of MAYNARD et al (1977) were obtained over an eastward electrojet (El no orthward) while those of CARLSON and KELLEY (1977) were obtained over a westward electrojet is of great importance in understanding the opposite con- This implies a change in electric field polarity from westward to eastward as one moves towards dawn.…”
Section: High Latitude Electric Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 23:00 UT when the electric field exhibited a peak, Tromsø was located on the pole side of the arc-like absorption structure, indicating that the large electric field was measured in the low electron-density region. This asymmetry near the auroral arc has been reported by many researchers (de la Beaujardiere et al, 1977Beaujardiere et al, , 1981Evans et al, 1977;Maynard et al, 1977;Stiles et al, 1980;Marklund et al, 1982;Ziesolleck et al, 1983;Opgenoorth et al, 1990;Doe et al, 1993;Aikio et al, 1993Aikio et al, , 2002Carlson et al, 1998;Johnson et al, 1998). On the other hand, at 22:00 UT when a small peak occurred in the particle heating rate, there was no notable absorption in the field-of-view of the imaging riometer.…”
Section: Eiscat Radar Measurementmentioning
confidence: 74%
“…CAHILL et al (1978) found threshold values of 15-20mVm-1 for the STARE radars. In the regions were an appreciable ionospheric current is due more to high conductivities than to high electric fields, as, for example, in auroral arcs (WESCOTT et al, 1969;DE LA BEAUJARDIERE et al, 1977;EVANS et al, 1977;MAYNARD et al, 1977;LENNARTSON, 1977), one may not observe any radar auroral irregularities because of subthreshold electric fields. Hence, it should be cautioned that the inability to measure weak electric fields in high conducting regions will lead to some possible errors in our determination of the three-dimensional current systems.…”
Section: Instrumentationmentioning
confidence: 99%